POTENSI ANTIINFLAMASI EKSTRAK BATANG WUNDU WATU (Alpinia monopleura) TANAMAN ENDEMIK ASAL SULAWESI TENGGARA SECARA IN VITRO - Musdalipah; Austin Tee, Selfyana; Wibawa Mahatva Yodha, Agung; Reymon; Azdar Setiawan, Muh.; Karmilah; Oktaviani, Santi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The wundu watu plant (Alpinia monopleura), is one of the endemic plants typical of Southeast Sulawesi which is commonly found in South Konawe Regency. The results of previous research on the essential oil content of the leaves and fruit of wundu watu are Î±-caryophyllene, Î²-pinene, limonene, Î±-pinene, Î²-caryophyllene and caryophyllene oxide. The essential oils of the leaves and fruit show antibacterial, antioxidant and anti-inflammatory properties. Pharmacological studies of this plant are not widely known, especially its efficacy as an anti-inflammatory. The purpose of this study was to determine the anti-inflammatory potential of extracts and fractions of wundu watu stem against inhibition of protein denaturation in Vitro. Wundu watu stem extract was extracted by maceration method using methanol solvent and ethyl acetate fraction. Anti-inflammatory testing using the protein denaturation inhibitor method using bovine and albumin and measured on a UV-Vis Spectrophotometer at a wavelength of 660 nm. The results showed that the extract and ethyl acetate fraction of wundu watu stem had anti-inflammatory activity with IC50 values of 10.59 mg/L and 2.02 mg/L. Based on the test results, it can be concluded that the stem extract of wundu watu has anti-inflammatory potential against protein denaturation with a very strong category.